As Below, So Above: Skaði: A True and Mythological "Other" - Feldman, David T., 1990- (2015)
Though she does not appear as often as other gods in Snorra Edda, the goddess Skaði causes a stir in the academic community whenever she does. The reason for this is due to how peculiar a character she proves to be, from her demanding compensation her for the death of her father to the matter of her very name and its masculine stem, not to mention the possibility of it being linked to Scandinavia itself, as the likes of Franz Rolf Schröder and Georges Dumézil have explored. Turville-Petre has also noted how Skaði’s similarity with the god Ullr is a point of interest. Skaði exhibits so many characteristics of an “other” figure, that it is hard not to see her otherness as being at the heart of her peculiarity as a goddess and a character in the myths. Focusing on Skaði and her significance as an “other,” this thesis will delve deeper into the nature of Skaði as a figure in the mythology as well as address the possibility of Skaði being an assimilated deity, most likely due to cross-cultural interaction with the Sami, the quintessential “others” of the Norse world, with whom Skaði is still most often identified. Keywords: Skaði, mythology, folklore, Ullr, Snorra Edda, assimilation, cross-cultural interaction, Sami, “others” Enda þótt Skaði sé ekki jafn áberandi og önnur goð í Snorra Eddu veldur hún jafnan miklum úlfaþyt meðal fræðimanna í hvert skipti sem hún birtist í heimildum. Ástæða þess er hversu sérstök persóna hún reynist vera, allt frá því að hún krefst bóta vegna dauða föður síns til þess að nafn hennar lítur út eins og karlkynsorð, svo ekki sé minnst á að nafnið hefur verið tengt við heiti Skandinavíu í fræðum Franz Rolf Schröder og Georges Dumézil. Turville-Petre benti einnig á áhugaverð líkindi hennar með Ulli. Skaði ber svo mikil merki þess að tengjast „hinum“ að það er ógjörningur annað en að líta á það sem eitt af einkennum hennar sem gyðju og persónu í goðsögunum. Með því að rýna í hlutverk Skaði sem eina af „hinum“ er í þessari ritgerð reynt að kafa dýpra í eðli hennar og stöðu í goðafræðinni um ...